Perencanaan Pemanfaatan Potensi Limbah Kepala Sawit Sebagai Sumber Energi Listrik di Kepulauan Bangka Belitung - Siti Rahmah Wati; Welly Yandi; Wahri Sunanda (Jetri : Jurnal Ilmiah Teknik Elektro, 2023)
Province of the Bangka Belitung Islands has the potential for palm oil commodities which contribute to the economy. Palm oil processing produces biomass waste such as shells, fibers, and empty fruit bunches. Biomass in the Province of the Bangka Belitung Islands has a potential of 217.7 MW. CO₂ emissions are mostly from burning fossil coal where the CO₂ produced is dangerous. Alternatives are needed to reduce these CO₂ emissions. One of them is biomass. This plan uses a forecasting method to get an estimate of the energy potential of palm oil waste in 2022-2032 in the Province of the Bangka Belitung Islands and CO₂ emissions generated from palm oil waste energy. By using modeling, evaluating methods, forecasting, and calculating energy potential as well as CO₂ emissions from biomass, it can be concluded that the projected energy potential of palm oil waste from 2022 to 2032 will increase every year and can help fulfill regional energy requirements for the Bangka Belitung Islands Province. In 2025 the energy produced by 15.29 thousand TOE can help meet the energy requirement of 27.91 thousand TOE 2025. In 2030 the energy produced by 28.12 thousand TOE can help fulfill 46.79 thousand TOE of energy 2030. CO₂ emissions The amount of biomass from palm oil waste in 2022-2032 is increasing every year along with the increase in energy produced from palm oil waste biomass. Keywords: oil waste energy, biomass, energy, CO2 emissions